Abstract 272: Effect of Level of Education on Outcomes of Mechanical Thrombectomy - Wilson Rodriguez; Gunjanpreet Kaur; Karthik Narayanan; Yongzhen Chen; Xiaoyi Gao; Jordan Scott; Aimalohi Esechie; Kara Christopher; Brian Miremadi (Stroke: Vascular and Interventional Neurology)
Introduction Multiple epidemiological studies have investigated the association between stroke clinical outcomes and education level. However, the relationship between the level of education in patients who underwent mechanical thrombectomy (MT) is limited. We aim to assess if the level of education is associated with poor functional outcome, defined as a modified Rankin Scale (mRS) score of ≥3, in patients following MT. Methods We reviewed 257 patients with large vessel occlusion (LVO) who underwent MT between 2018 and June 2023, education levels were available on 106 patients. Education level was defined as “less than high school” (n=15, 14.2%), “high school” (n=54, 50.9%), and “college or higher” (n=36, 34%), 1 of these with “other” education level was excluded from the analysis. Chi‐square and Kruskal Wallis tests were used to examine potential differences in education level and outcomes. All analyses were conducted in IBM SPSS Statistics version 29. Results Compared to those with a college or higher education, those with a less than high school education were more likely to have a poor functional outcome (mRS ≥3) at 90 days. (p=0.03). Black patients were more likely to have a less than high school education than white patients (30.0% vs 4.8%) p<0.001. There were no significant differences in mortality, length of hospitalization, comorbid conditions, Alberta stroke program early CT score (ASPECTS), or initial National Institutes of Health Stroke Scale (NIHSS). Conclusion In our cohort, patients with less than a high school education are more likely to have poorer functional outcomes 90 days post‐MT compared with patients with a college education or higher. Interestingly, there was no significant statistical difference noted in initial NIHSS, ASPECTS, and length of hospitalization between these cohorts. Larger post‐thrombectomy cohorts should be used to further investigate these initial results. In addition, it is important to note that education and race are intertwined in this study, though our relatively small sample of post‐thrombectomy patients limited our analyses. Future research should evaluate this relationship further.